SOUND DATA - Narzullayev Shahzad Tohir ugli (Web of Journals Publishing, 2025)
Sound information occupies an important place in our lives.They allow us to provide information about the world around us, gain knowledge, communicate with other people and perform many other tasks.
Keywords: Virtual and additional reality, neurointerfaces, sound data, anologous sound, macromedia flash 8 program, digital sound.